HUBUNGAN TINGKAT PENDIDIKAN, TINGKAT PENGETAHUAN DAN POLA ASUH IBU DENGAN WASTING DAN STUNTING PADA BALITA KELUARGA MISKIN - Cholifatun Ni’mah; Lailatul Muniroh (Media Gizi Indonesia, 2015)
Children under five is a group that vulnerable to undernutrition, particularly wasting and stunting. Wasting and stunting are common happened in poor families. One cause of wasting and stunting is related to mother care pattern to their child. Mother care pattern is associated to maternal education and knowledge level. Mothers with low education will be more difficult to receive information compared to mothers with higher education. Less knowledge mother may affect poor caring pattern, therefore it could induce wasting and stunting problem in children under five. The aim of this research was to analyze correlation between the level of education, knowledge, and mother’s care pattern with wasting and stunting. The sample was 47 children from poor families in Balen, Bojonegoro that selected using simple random sampling technique. Data were analyzed using chi-square test with α=0,05. The result of the research showed that in poor families, percentage of stunting was higher than wasting and there was no correlation between level of education (p=0,581 and 0,605), level of knowledge (p=0,632 and 0,963), and mother’s care pattern (p=0,719, and 0,928) with wasting and stunting. This study concluded that the level of education, knowledge, and mother’s care pattern do not contribute to the occurrence of wasting and stunting problem among children under five from poor families in Balen, Bojonegoro. The government should strive to increase mother’s and pregnant women’s knowledge about balanced nutrition, child health, and child nutritional problem to prevent wasting and stunting through routine promotion and counselling by health professionals.Keywords: poverty, stunting, wasting